A case of an old age postmenopausal woman with a giant myoma uteri - (:unkn) unknown (My University, 2001)
We report here, the case of an old age postmenopausal woman with a giant myoma uteri. Ultrasonographic features, clinical presentations, differential diagnosis and treatment modalities of this rare case are presented and discussed.
Keywords: Leiomyoma uteri; Menopause